Exploring the Use of Digital Technology in English Language Teaching: Strategies and Methods for Effective Implementation - Octaberlina, Like Raskova (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
The globalization of technology, including education, has impacted all facets of life. Therefore, English learning strategies must be studied so teachers can easily choose and determine English learning strategies for teaching students digital base technology. This research aims to describe (1). Digital technology in the world of education; (2). Digital technology-based English learning methods; (3). Digital technology in the development of language learning skills. Hence, this study applied library research methods through gathering research article by utilizing Publish-or-Perish application. The results of this study are (1). Technology supporting education is expected to assist students and educators in carrying out teaching and learning activities in schools; (2). At this time, many English learning methods have been integrated with digital technology. Such as utilizing digital technology using the direct method and others; (3). The use of digital technology is also used in developing students' English skills (listening, speaking, reading, and writing), for example, the use of YouTube videos, digital posters, digital comics, and Grammarly tools. Henceforth, this study urges the ELT teachers to leverage their digital technology competences as well as their pedagogy to attend meaningful and engaging learning for their students.